P0942HYPOXEMIA AND UREMIA INDUCE OXIDATIVE IMBALANCE IN ENDOTHELIAL CELLS. (6th June 2020) - Moreno-Amaral, Andrea N; Carvalho Silva, Caroline; Andrade, Gabriela Bohnen; Monteiro, Julia; Grobe, Nadja; Silva Pecoits Filho, Roberto Flavio; Stinghen, Andréa E M; Kotanko, Peter
Abstract: Background and Aims: Intradialytic hypoxemia is associated with oxidative stress, endothelial dysfunction, inflammation, higher erythropoietin requirements, and higher all-cause hospitalization and mortality in hemodialysis (HD) patients (Meyring-Wosten, et al., 2016). The aim of the present study was to further expand our insights into the hypoxia-uremia axis by investigating the oxidative balance in endothelial cells (EC) under hypoxic and uremic conditions. Method: Human umbilical EC were incubated with DMEM medium supplemented with 10% of fetal bovine serum (FBS; control) or with sera obtained from healthy subjects (S-CON) or HD patients (S-HD, 1:10), respectively, for 40 minutes, 4 hours, and 24 hours under normoxic (21% O2 ) or hypoxic (5% O2 ) conditions (Culture Chamber ProOx, Biospherix). EC were analyzed by flow cytometer (BD Accuri™ C6 Plus) to assess a) intracellular production of reactive oxygen species (ROS, DCFH-DA probe, Abcam); b) reduced glutathione (GSH) content (ThiolTracker Violet probe, Thermo Fisher Scientific). Results: S-HD increased intracellular ROS production at all time points compared to S-CON. Moreover, ROS production was higher under hypoxic conditions. ROS production declined after 24 hours. S-HD induced slightly higher GSH content when compared to S-CON in normoxia (Table 1). Conclusion: In our in vitro experiments, hypoxia and uremia jointly favor EC oxidative imbalance. This effect is particularly pronounced after 4 hours. Translational studies are warranted to explore the clinical relevance of our findings.